Level of Participative Leadership, Quality Culture, Job Satisfaction and Achievement Motivation Lecturer at the Faculty of Sports Science, Universitas Negeri Medan - Damanik, Suryadi; ., Suprayitno; ., Mesnan; Nasution, Usman (Journal of Ecohumanism, 2024)
This research aims to evaluate the level of participative leadership, quality culture, job satisfaction and achievement motivation of lecturers at the Faculty of Sports Sciences, Medan State University. The method used in this research uses descriptive methods and a survey research form. The population and sample in this research were 100 lecturers at the Faculty of Sports Science, Medan State University. The results of the research carried out showed that the participative leadership category showed that it was 80.20% in the "high" category. The quality culture category shows that it is 85.64% in the "high" category. The job satisfaction category shows that it is 70.30% in the "medium" category. The achievement motivation category shows that it is 73.27% in the "medium" category. This shows that although participative leadership and a culture of quality have been achieved well, there are challenges in increasing job satisfaction and achievement motivation of lecturers at the Faculty of Sports Science, Medan State University. These findings show the importance of strategic interventions to increase job satisfaction and achievement motivation, even though the basics of leadership and quality culture are already quite strong.